2023
DOI: 10.3390/resources12070076
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Municipal Waste Management during the COVID-19 Pandemic—A Case Study of Poland

Abstract: With the outbreak of the COVID-19 pandemic, the waste management sector had to face new challenges, e.g., changes in the size and composition of the waste stream, or the presence of potentially infectious waste. This article is based on a case study in Poland. The data analysis showed that the increase in municipal waste mass during the pandemic did not differ from statistics observed in previous years and ranged from 0.3 to 0.5 million tons per year. Lifestyle changes caused a decrease in the amount of waste … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Past research has frequently emphasized that increased waste generation during COVID-19 will negatively impact the environment, creating health hazards. However, some studies claim that the pandemic has had little impact on MSW waste amount [ 12 , 24 ]. The important contribution of the current study is that it shows that not all wastes at the local level increased during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Past research has frequently emphasized that increased waste generation during COVID-19 will negatively impact the environment, creating health hazards. However, some studies claim that the pandemic has had little impact on MSW waste amount [ 12 , 24 ]. The important contribution of the current study is that it shows that not all wastes at the local level increased during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Third, medical or hospital waste increased sharply, necessitating improved medical waste management. A recent study by Urbańska et al [ 12 ] found that, at the national level, MSW amounts did not differ much from those of the pre-COVID-19 era. Requena-Sanchez et al [ 13 ] investigated household behaviors in six Latin American countries and found that participants in the study did not report major waste composition changes before or during the pandemic.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation